Effects of oral and intravenous midazolam, triazolam and flunitrazepam on the sleep-wakefulness cycle of rabbits - Scherschlicht, R. (1983)
1 The effect of the new, short-acting benzodiazepine, midazolam as well as that of triazolam and flunitrazepam on the sleep of rabbits was recorded for 6 h. 2 Midazolam at 1 mg kg(-1) i.v. augmented both rapid eye movement sleep (REMS) and non-REM sleep (NREMS) only in the first half of the observation period. At 10 mg kg(-1) i.v., NREMS was further increased in the first and, to a lesser degree, in the second 3-h period, while REMS was suppressed. Both doses were less effective orally than intravenously. 3 Qualitatively, the effect of triazolam 0.01 and 0.1 mg kg(-1) i.v. was very similar to that of the corresponding low and high intravenous doses of midazolam, except that the high dose of triazolam had a prolonged effect on total sleep time. Like midazolam, triazolam was substantially less effective orally than intravenously. 4 Flunitrazepam at 0.1 and 1 mg kg(-1) i.v. produced almost the same effects as midazolam and triazolam at the respective low and high intravenous doses, but had a longer duration of action. In contrast to midazolam and triazolam, flunitrazepam was almost as active orally as intravenously.